Implementation of accounting based financial governance as an effort to improve msmes tempeh creacker Bu Erna - Cindy Arfiana; Wardayani Wardayani (Enrichment : Journal of Management, 2023)
This research is entitled "Implementaion of Accounting Based Financial Governance as an Effort to Improve MSMEs tempeh crecker Bu Erna" which aims to help these tempeh cracker MSME actors to have good and correct financial governance. This research was conducted on MSMEs tempeh crecker Bu Erna using qualitative methods, where this study will manage data from the data obtained which will later be explained in such a way. The financial statements obtained are already good, but the management applied by MSME actors tempeh crecker Bu Erna is still not optimal.